Assessing the relationship between a body shape index and mortality in a group of middle-aged men. Issue 5 (October 2017) - He, Sen; Zheng, Yi; Wang, Hua; Chen, Xiaoping
Summary: Background & aims: Recently, a new anthropometric parameter emerged, namely A Body Shape Index (ABSI), which appears to be a major risk factor for mortality in the American and British populations. To the best of our knowledge, the relationship between ABSI and mortality was not studied previously in the middle-aged Chinese men. Therefore, we assessed the relationship based on a 15-year prospective study. Methods: In an urban community of Chengdu, 780 middle-aged Chinese men were included in 1992 and followed up for 15 years. Results: During the follow-up, 29 subjects died (mortality rate: 3.7%), and ABSI tended to be linearly associated with mortality. The subjects could be categorized into five groups by the quintiles of baseline ABSI, as follows: the first quintile (Q1), the second quintile (Q2), the third quintile (Q3), the fourth quintile (Q4) and the fifth quintile (Q5). Across the quintiles, the mortality rates were 3.8%, 5.3%, 3.0%, 4.7% and 1.9% in Q1, Q2, Q3, Q4 and Q5, respectively ( p trend = 0.386). With the highest quintile (Q5) as reference, univariate and multivariate Cox regression analyses presented that ABSI was not associated with mortality. Conclusions: ABSI, a new anthropometric parameter, might not be associated with mortality in the middle-aged Chinese men. Further studies are needed to explore the specificities of ABSI in different populations.